Technical Analysis Ballast Water Treatment By Using Economizer Utilizing Main Engines Exhaust Heat To Comply With International Ship Ballast Water Management At Mv. Leader Win - Hari Prastowo; Djoko Paritono Widodo; Semin .; Wiwin Rohmawati (International Journal of Marine Engineering Innovation and Research, 2017)
Based on the International Ballast Water Management regulations (IBWM), waste water ballast itself has the attention of some researchers to reduce the amount of waste species present in the ballast water with a variety of methods, as of biological, physical, mechanical, and chemical. The decision-making tools such as ballast water heater, flow-through system and others where possible these tools can minimize waste species in ballast water at a certain temperature or pressure of the flow according to the calculations. This study was aimed to calculate and analysis the effectiveness of the system treatment between Option 1 (Economizer & Bundle) and Option 2 (Economizer & Heat Excharger) then it will compare. First option is using economizer and bundles to transfer a heat from a source heat of exhaust gas then medium by thermal oil circulated. The second option is using economizer and heat excharger where a same heat source , but sea water from ballast tank sirculated to heat excharger. And from economizer to heat excharger is using thermal oil as a heat medium. For all calculation and anaalysis is using softwere HTRI. First option having a duty 2.503 MegaWatts at economizer and 1.9567 MegaWatts at bundles. Over design 2.01% at Economizer and 7.1%5 at bundles. Pessure drop 63.287 kPa at thermal oil after economizer and 68.196 kPa after bundles. Treatment time to this option is 44.424 hors. Second option having a duty 3.38 MegaWatts at economizer and 3.1227 MegaWatts at heat excharger. Over design 5.85% at Economizer and 3.49%5 at heat excharger. Pessure drop 38.697 kPa at thermal oil after economizer and 28.476 kPa after heat excharger. Treatment time to second option is 42.03 hours. Option 2 (Economizer & Heat Excharger) is more optimum than option in analytical techniques. By analysis of treatment system, are expected this thesis can be applied to either the MV. Leader Win Vessel to comply with the operational needs according to standard employability.